19+9b=-3(8b-2)

Simple and best practice solution for 19+9b=-3(8b-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19+9b=-3(8b-2) equation:


Simplifying
19 + 9b = -3(8b + -2)

Reorder the terms:
19 + 9b = -3(-2 + 8b)
19 + 9b = (-2 * -3 + 8b * -3)
19 + 9b = (6 + -24b)

Solving
19 + 9b = 6 + -24b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '24b' to each side of the equation.
19 + 9b + 24b = 6 + -24b + 24b

Combine like terms: 9b + 24b = 33b
19 + 33b = 6 + -24b + 24b

Combine like terms: -24b + 24b = 0
19 + 33b = 6 + 0
19 + 33b = 6

Add '-19' to each side of the equation.
19 + -19 + 33b = 6 + -19

Combine like terms: 19 + -19 = 0
0 + 33b = 6 + -19
33b = 6 + -19

Combine like terms: 6 + -19 = -13
33b = -13

Divide each side by '33'.
b = -0.3939393939

Simplifying
b = -0.3939393939

See similar equations:

| x+x+9000=3700 | | -40=4x+6(-5x+15) | | 17t-87=4t+17 | | 5x-3x+x+8=2x+1 | | 4=(19-2x) | | (4x-1)2+(6x+9)2=a | | 8b-68=2b+10 | | -2=(3x+10) | | 4+4x+4-x=22 | | 35=-5+4(s+6) | | 0.79b-1.19b=-24 | | 3s-94=s | | 2q+72=180 | | -56=90.32 | | 3b+5+1a= | | 2m-11=3 | | y=12-2(3) | | -16=5y+3y | | 6a+2.3=-9.7 | | 95x=25x+70 | | n+3q=15 | | y=12-2(2) | | 4+2x+2-x=9 | | 90+20+2x+3x= | | -6(5x+2)=188 | | 2t+9=t+11 | | 122x=22x+100 | | -8a-3+4a=33 | | 1.8a=-9.18 | | c-7=3c-33 | | x^2-4*x=10 | | 33x=5(3x+18) |

Equations solver categories